To find what the function \( g(x) = -f(-x) \) will look like, we first need to analyze the original function \( f(x) = 2(x + 2^2) \).
-
Simplifying the function: \[ f(x) = 2(x + 4) = 2x + 8 \]
-
We will compute \( g(x) = -f(-x) \): \[ f(-x) = 2(-x + 4) = -2x + 8 \] Thus, \[ g(x) = -(-2x + 8) = 2x - 8 \]
Now, we can calculate \( g(x) \) for the values \( x = 1, 2, \) and \( 3 \):
- For \( x = 1 \): \[ g(1) = 2(1) - 8 = 2 - 8 = -6 \]
- For \( x = 2 \): \[ g(2) = 2(2) - 8 = 4 - 8 = -4 \]
- For \( x = 3 \): \[ g(3) = 2(3) - 8 = 6 - 8 = -2 \]
Thus, we find: \[ g(1) = -6, \quad g(2) = -4, \quad g(3) = -2 \]
Now let's look at the tables provided to see which one reflects this behavior. We can see that:
-
First table:
- \( g(1) = 2 \)
- \( g(2) = 0 \)
- \( g(3) = 2 \)
-
Second table:
- \( g(1) = -2 \)
- \( g(2) = 0 \)
- \( g(3) = -2 \)
-
Third table:
- \( g(-1) = -2 \)
- \( g(-2) = 0 \)
- \( g(-3) = -2 \)
-
Fourth table:
- \( g(-1) = 2 \)
- \( g(-2) = 0 \)
- \( g(-3) = 2 \)
None of the provided tables match the calculated values \( g(1) = -6 \), \( g(2) = -4 \), and \( g(3) = -2 \).
However, if we were to summarize the correct form of how \( g(x) = -f(-x) \) transforms the points, we could infer that it would provide a reflection about the origin when we consider the transformations in the context of the original points of the graph of \( f(x) \).
Since none of the options provided correctly reflect the calculations.
Please double check the setup or provide clarification on the specific points or transformations you would like to focus on.